TERRITORIAL FORMATION OF THE GUIANAS REGION - Silva, Gutemberg de Vilhena; Granger, Stephane (Ra'e Ga: o Espaço Geográfico em Análise, 2021)
For more than 9,500 years, the indigenous people reigned supreme in the construction of territorialities in the Guiana region, a part of the Amazon between the Orinoco and Amazon rivers, which borders the Atlantic Ocean. With the encounter of both worlds, a metaphor that refers to the contact of the indigenous people with the European explorers, everything changed and the last five centuries have been marked by wars, killings, and various territorial restructurings in the Guianas. Through a geopolitical perspective as a methodological fulcrum, and anchored in literature review and thematic cartography, this text examines the local-global relationship of the region over the five centuries of contacts, demarcating important facts and contexts in Europe that imprinted significant changes on the political space of the Guianas. Of the relevant moments, the great navigations, the bourgeois revolutions, and the Cold War were the most important for the transformations that occurred in the region. In addition, boundary treaties played a crucial role, with special attention to two of them: the Treaty of Tordesillas (1494) and the Treaty of Madrid (1750). The text concludes that the search for riches and moments of instability in Europe, whether due to territorial recompositions there or conflicts, determined important reorganizations in the Guianas that made it what it is today, a complex region from the geopolitical point of view.